2018
DOI: 10.1111/1467-8489.12247
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agricultural innovation adoption: a meta‐analysis

Abstract: The impacts of adopting agricultural innovation and technology are widely examined. This paper synthesises 154 studies, which yielded a total of 600 estimates of the impact of adopting agricultural innovation and technology on production, social and economic outcomes. Using meta‐regression analysis, the empirical results show that the reported impact of adopting agricultural innovation and technology rises significantly over time, notwithstanding a significant publication bias. Whether studies find significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 26 publications
1
34
0
3
Order By: Relevance
“…Most studies have demonstrated a positive impact of adoption of improved maize varieties on maize yields, except that of Takam Fongang (2017), who found no significant impact. More recently, Ogundari and Bolarinwa (2018) used meta regression analysis to investigate variations in the estimates of the impacts of adopting agricultural innovations and technologies on production, economic, and social outcomes across developing countries, and showed a preponderance of studies focusing on the impact of high-yielding varieties over those focusing on agricultural technologies such as agricultural conservation. Although such studies have reported a positive impact of adoption of high-yielding varieties such as improved maize varieties on maize yields, some studies have noted a decreasing effect of adoption of improved seeds over time (Wu, Ding, Pandey, & Tao, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have demonstrated a positive impact of adoption of improved maize varieties on maize yields, except that of Takam Fongang (2017), who found no significant impact. More recently, Ogundari and Bolarinwa (2018) used meta regression analysis to investigate variations in the estimates of the impacts of adopting agricultural innovations and technologies on production, economic, and social outcomes across developing countries, and showed a preponderance of studies focusing on the impact of high-yielding varieties over those focusing on agricultural technologies such as agricultural conservation. Although such studies have reported a positive impact of adoption of high-yielding varieties such as improved maize varieties on maize yields, some studies have noted a decreasing effect of adoption of improved seeds over time (Wu, Ding, Pandey, & Tao, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In de landbouwwetenschappen zijn er veel studies gedaan naar de adoptie van nieuwe technologieën door boeren (Chavas & Nauges, 2020;Feder & Umali, 1993;Ogundari & Bolarinwa, 2018). Ook voor aquacultuur zijn er dergelijke studies uitgevoerd (zie bijvoorbeeld Kumar, Engle, & Tucker, 2018).…”
Section: Haalbaarheidsfactorenunclassified
“…Agricultural innovation can also be defined as a form of the package given to people especially farmers to improve agricultural productivity of their farm enterprises. The package can come in form of training on agribusiness, benefits given to farmers through the improvement of their soil fertility, conservation of soil nutrients, water and other natural resources, raising yields, improving pest management, decreasing effects of climate change and supporting other agricultural mechanisms (Ogundari & Bolarinwa, 2018). In the same vein, Food and Agricultural Organisation of the United Nations (2018) defined agricultural innovation as the process whereby individuals or organizations bring new or existing products, processes or ways of organization into use for the first time in a specific context in order to increase effectiveness, competitiveness, resilience to shocks or environmental sustainability and thereby contribute to food security and nutrition, economic development or sustainable natural resource management.…”
Section: Literature Reviewmentioning
confidence: 99%